2D Titanium Carbide/Reduced Graphene Oxide Heterostructures for Supercapacitor Applications. Issue 1 (20th April 2018) - Navarro‐Suárez, Adriana M.; Maleski, Kathleen; Makaryan, Taron; Yan, Jun; Anasori, Babak; Gogotsi, Yury
Abstract: Solution‐processable two‐dimensional (2D) materials offer the possibility of manufacturing heterostructures with various properties, creating a way to tune materials towards a specific application. Two different 2D materials, titanium carbide MXene (Ti3 C2 T x ) and reduced graphene oxide (rGO), have shown promising results for supercapacitor applications due to their flake‐like morphology, high conductivity; and ability to intercalate molecules or ions for charge storage. Here, we demonstrate the self‐assembly of a heterostructure between negatively charged Ti3 C2 T x and positively charged modified rGO after shear mixing. Changes in zeta ( ζ ) potential, X‐ray diffraction (XRD) patterns; and Raman spectra confirm the assembly of this heterostructure. The produced rGO : Ti3 C2 T x heterostructures were used as electrodes for supercapacitors. The addition of rGO to Ti3 C2 T x allowed some widening of the voltage window. Moreover, due to the synergistic effect of these materials, an increase of the capacitance value was observed. An electrode film composed of rGO (1 wt.%) and Ti3 C2 T x (99 wt.%) achieved capacitance values up to 254 F ⋅ g −1 at 2 mV ⋅ s −1 and 193 F ⋅ g −1 at 100 mV ⋅ s −1 . Abstract : Layer cake : A heterostructure between negatively charged Ti3 C2 T x and positively charged modified rGO is synthesized through self‐assembly. The rGO : Ti3 C2 T x heterostructure exhibits a wider voltage window and higher capacitance than Ti3 C2 T x, suggesting promising applications in energy storage devices.